Types of meaning in the stories of Nazar Eshanqul - O'rolova Mashhura Hamid qizi; Ubaydullayeva Shohista Hidoyatullo qizi (Peerian Journals Publishing, 2023)
When every creator steps into the world of literature, he deeply feels the complex aspects of the art of poetry and strives to take his place in the field of literature. It is distinguished by its style. Literary critic Umarali Normatov writes about this: "The reason for every creative event in our national literature should be sought not from external factors, but first of all from within this national soil, from the real reality, from the demands of the time... "This principle is especially evident in the works of Nazar Eshanqul. Ladi
Keywords: meaning transfer; metonymy; metaphor; synecdoche